The impact of the information environment on students - Kraieva, O. V. (ТДАТУ, 2019)
Summarizing all of e, we can notice that it is important to pay more attention to improve the information environment, to come up with ways how to filter it and develop skills to focus only on necessary facts. Otherwise, with the further development of technology, the problem can only worsen and bring a lot of problems.
Keywords: information environment; clogging of information resources; Internet; students